Human Interruption Management in Workplace Environments: An Overview - Alkahtani, M.; Abidi, M. H.; Ahmad, A.; Darmoul, S.; Samman, S.; Ghaleb, M. (Engineering, Technology & Applied Science Research, 2020)
Interruptions are unexpected breaks that introduce new tasks on top of ongoing activities. In work environments, interruptions occur when operators and decision-makers have to deal simultaneously with several stimuli and information sources and have to make decisions so as to maintain the flow of activities at a satisfactory level of performance or quality of service. The causes and effects of interruptions and their subsequent management strategies in workplace environments have been researched in the past, however, only a few review articles are available to report on current advances in this area, to analyze contributions, and to highlight open research directions. This paper offers an up-to-date review and a framework for interruptions and interruption management strategies. The current approaches to identify, report, and manage interruptions in a variety of workplace environments are reviewed and a description of environmental characteristics that favor the occurrence of interruptions and influence interruption management in workplace environments is provided. Various approaches to classify and model the different types of interruptions and their cause-consequence relationships are discussed and the strategies to manage interruptions and approaches to measure human performance when dealing with interruptions are analyzed. Based on these insights, several guidelines to manage interruptions in workplace environments are provided, and future research directions are highlighted.